2022
DOI: 10.1002/slct.202200168
|View full text |Cite
|
Sign up to set email alerts
|

Porous Structure Controlling the Selectivity of Oxygen Reduction Reaction on N‐Doped Carbon in Alkaline Solution

Abstract: N-doped carbon materials have been regarded as potential replacements for Pt-based electrocatalysts for oxygen reduction reaction (ORR). However, the exact catalytic mechanisms are still not completely understood and there is a controversy about which type of N determines the selectivity of the reaction. This study reports a simple pyrolysis method to prepare hierarchical porous-structured N-doped graphene using 4-nitroimidazole as both C and N sources without the presence of two-dimensional template. The as-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…52 Also, N-doped platelet-like carbon consisting of micropores prefers the 2e − ORR pathway with high selectivity toward H 2 O 2 generation over 90% in the potential range of 0.20–0.62 V vs. RHE. 53 The well-ordered mesoporous structure of nitrogen-doped carbon with diameters of 3.4–4.0 nm was reported to exhibit high selectivity toward H 2 O 2 due to enhanced mass transport in the catalyst layer. 54 Meanwhile, the honeycomb carbon nanofibers with super hydrophilic O 2 -entrapping surfaces are capable of achieving a high H 2 O 2 selectivity of 97.3%, much higher than that of their solid carbon nanofiber counterparts.…”
Section: Selectivity During the Cathodic Reduction Processmentioning
confidence: 99%
“…52 Also, N-doped platelet-like carbon consisting of micropores prefers the 2e − ORR pathway with high selectivity toward H 2 O 2 generation over 90% in the potential range of 0.20–0.62 V vs. RHE. 53 The well-ordered mesoporous structure of nitrogen-doped carbon with diameters of 3.4–4.0 nm was reported to exhibit high selectivity toward H 2 O 2 due to enhanced mass transport in the catalyst layer. 54 Meanwhile, the honeycomb carbon nanofibers with super hydrophilic O 2 -entrapping surfaces are capable of achieving a high H 2 O 2 selectivity of 97.3%, much higher than that of their solid carbon nanofiber counterparts.…”
Section: Selectivity During the Cathodic Reduction Processmentioning
confidence: 99%
“…[13][14][15][16] What is more, both four-electron (4e À ) and two-electron (2e À ) ORRs can be achieved in N-doped carbon catalysts, and the origin of ORR selectivity is still poorly understood to date. [19][20][21][22] Since thermodynamics favors the 4e À ORR over the 2e À ORR, the selectivity should originate in the kinetics of ORR in N-doped carbon. [21] Our previous work has shown that the ORR selectivity in alkaline electrolyte is dependent on the H 2 O transfer dynamics which are controlled by the porous structure of N-doped carbon catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Our previous work has shown that the ORR selectivity in alkaline electrolyte is dependent on the H 2 O transfer dynamics which are controlled by the porous structure of N-doped carbon catalysts. [22] Facile accessibility of H 2 O molecules to the active sites is essential to reduce the adsorbed O 2 to OH À completely. N-dope carbon with abundant porous structure allows the desired 4e À ORR due to the fast H 2 O diffusion, whereas N-doped carbon with only limited micropores exhibits 2e À ORR since there are not enough H 2 O molecules to reach the active sites for a complete 4e À ORR.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations